Innovation in Bioinformatics: Recent tools, Database and Involvement of Artificial Intelligence - Ahmed, Aziz; Shuaib, Mohd; Banga, Abdulbasid; Ahmad, Rizwan (UI Scholars Hub, 2024)
Bioinformatics has evolved in recent years into a crucial subject and a well-liked research area that is interconnected with many approaches and disciplines. The capacity of bioinformatics and its approaches to tackle challenging biological problems and promote research and development. There are various tools and database which are used in bioinformatics. AI is the capacity of a computational system to carry out various activities associated with intellectual beings and as a computer system's imitation of human intelligence processes. The bioinformatics applications with artificial intelligence have the capacity to annotate the data in the direction of logical conclusions. By combining AI and bioinformatics molecular dynamic simulations, molecular docking studies, annotations of biological sequences, computational drug design, and gene prediction can be analyzed effectively. The structural bioinformatics tools with artificial intelligence (AI) are effective approaches for designing novel active chemicals to treat neurological diseases and cancer. Immunoinformatics, vaccinology, health informatics, medical informatics, medical science, and pharmaceutical sciences are just a few of the health sciences that have benefited greatly from advances in AI and bioinformatics. Future developments in omics and other fields are predicted to generate large amounts of data quickly, and bioinformatics will be essential in managing, analyzing, and discovering new uses for this data. Bioinformatics will be crucial in saving time and costs by applying AI to examine the massive data sets. Additionally, it will hasten biological discoveries, particularly those related to health, biomedical research, and robotic surgery.